Esquema para a tradução de aplicações entre as linguagens Circus e Safety Critical Java - Leidemer, Nathan (2016)
At safety-critical, mission-critical and business-critical systems the high cost of failure makes required the use of methods and techniques to ensure application reliability. In this context, formal languages, as Circus or specific languages versions like Safety-Critical Java, were created to facilitate the verification and validation of applications so consequently assisting to increase the overall reliability. Despite of the reliability increase, the modeled systems in formal languages can not be executed subsequently has to be implemented in a traditional programming language. It is in this process of free translation where occur most mistakes that end up not ensuring that the generated code conforms to the specification. Based on that premise, this paper propose to expound a strategy of translation from models written in Circus language to executable programs in SCJ language. Among the main objectives and contributions include the creation of EBNFs of the two languages and the detailed description of the translation of all elements between the two languages.